Review of Nikolas Rose’s The Politics of Life Itself: Biomedicine, Power, and Subjectivity in the Twenty-First Century - Lekka, Vasia (Historein, 2013)
Review of Nikolas Rose’s The Politics of Life Itself: Biomedicine, Power, and Subjectivity in the Twenty-First Century